Pedestrianization of a city core and the light rail transit - Eugenio, Victoria A. 1945- (1984)
This study tries to relate pedestrians' behavioral pattern demands and needs with the physical environment of a city core as the setting for their activities. The intention is not only to make the conditions better for the pedestrians but also to recommend ways by which the blighted city core may be improved. In general, this study seeks to formulate a set of design criteria and to resent a design concept for the pedestrianization of the core of the city of Manila. Specifically, this study aims: a) to understand the pedestrians' special needs by looking into pedestrian bahavior, the problems confronting them, the inconveniences experienced by them, and the extent to which their ability to move about freely is affected by traffic; b) to assess and evaluate all redevelopment proposals and plans for the area with the pedestrians' special needs in mind; an c) based on (a) and (b) above, to explore ways by which the area might be redesigned. Because the Quiapo-Sta. Cruz area in the City of Manila serves both as a religious and a commercial center, people have tended to concentrate there, resulting in a high pedestrian population density. With the operation of the LRT, still more people are expected to converge there since the 11th station is located and already being constructed in Carriedo. The already high pedestrian population density there is therefore expected to be still higher. This., in turn, is expected to seriously hamper movement of both pedestrians and motor vehicles, which even without the LRT station, is already a problem. One way by which this problem may be met is to redesign the area. It is deemed important, however, that the area be so disigned as to give priority to the movement and comfort of people, "retaining for him his ability to move about freely as a member of a community and enabling him to do so in safety". To be able to achieve this, an understanding of his unique sensory capabilities and limitations is required. The study approach is primarily integrative, following an organized procedure. Direct observation and interviews are primary methods of gathering relevant in-depth information. Photography was extensively used but the principal tools were pads of paper, a pencil and a place to observe, following Whyte's methodology in his study of crowding New York and Tokyo (1976). Collection of other data was done by means of a Physical Environment Study and a Pedestrian Study. The main thrust of the planning approach is directed evolving a conceptual design that will provide an ergonomically wholesome environment for man - free from the danger and distraction of vehicles, yet accessible enough to various modes of transportation. The salient features of the approach are presented by means of the functional concept and the design concept. The former approach takes into account (a) accessibility, (b) functional traffic arrangement and (c) provision for pedestrian cases/malls. The latter establishes a set of design criteria without engaging in any detailed design activity. The objective of these guidelines is to be able to make use of the space freed from vehicular movement to best advantage with the pedestrian's needs in mind. The pedestrianized streets should be carefully designed as a pleasant and stimulating environment in itself and conforming to a design criteria formulated essentially for the study. The following are the general findings of the survey and observation conducted in the study area: highest pedestrian concentration is at Carriedo, Avenida Rizal and Villalobos-Quinta Market area; pedestrian movements are usually directed to where modes of transport are located with Carriedo serving as a mojor link to the major public transposrt route at Quezon Blvd. and Avenida Rizal; although LRT is viewed as a possible means of enhancing the income of business establishments in the future, the on-going construction is causing them considerable inconvenience and losses; the rerouted traffic flow through smaller, secondary streets where high pedestrian concentration and the crowding of ambulant vendors and hawkers are the most pressing problems experienced in the area; the pedestrianization of the area is looked up in as a favorable improvement in view of the needed change in the area. This study is necessary since the blight and continued decay of the Quiapo-Sta. Cruz areas has long been a matter of deep concern for city administrators and planners. With the expected operation of the LRT, the fear has been expressed that "the LRT may merely further blight downtown Manila, unless this area is transformed into something more than a transit point past which one rushes withot regret.." It is precisely with the transformation of the area that the study is concerned. It presents ways by which this may be made possible. It also presents an assessment of various government plans and programs for the area in the light of pedestrians' needs. This study is therefore timely and useful not only to planners and administrators involved in the Quiapo-Sta.Cruz area but, in general, to those involved in shaping and reshaping city cores and other areas of heavy pedestrian concentration. While this study analyzes the wide range of human activity occurring within a city core, it looks into the development of such a core, not only in relation to pedestrian needs, but also as a significant locus of change resulting from the introduction of a new transportation system such as Light Rail Transit System. The high concetration of people through which the LRT will run, particularly on specific portions where stations and terminals will be located are potential areas where changes will definitely occur. These stations and terminals will serve as catchment areas and increase the potential growth of comnmercial establishments. The Quiapo-Sta.Cruz area covered by this study is one such area. Since some kind of transformation will evidently occur, blight as a result of heavy pedestrian activity must necessarily be prevented by setting environmental and physical design concepts that will ensure a wholesome setting for both people and urban form. The study findings point to the need of pedestrians for adequate space to allow freedom of movement, convenience and safety. This is critically felt especially on Fridays, when devotees flock to the Quiapo Church, and on weekends when most families go out to shop or simple take walks in the downtown area for relaxation. The pedestrianization of the area is therefore a design concept that could provide a means by which the needs for freedom of movement as well as the safety of the pedestrians in the area may be achived. More importantly, the urban area and structures could be give a pleasant face-lift. Signs of revitalization as a result of heightened commercial growth and continued flow of investment from major business concerns is already evident. (e.g. McDonalds, Shakeys, Jolibee and Dunkin' Donuts have recently established their branches within the area). The rational development of the area therefore cannot be overemphasized.